ANALISIS FITUR SOSIOLINGUISTIK: PENGGUNAAN REGISTER DALAM WAWANCARA KOMERSIAL ONLINE DAN APLIKASINYA DALAM PENGAJARAN BAHASA INGGRIS - Riadil, Ikrar Genidal (Universitas Mahaputra Muhammad Yamin, 2025)
The language used in digital marketing, particularly on social media platforms like Instagram, reflects unique patterns that differ significantly from everyday spoken interaction. This study aims to explore how linguistic registers are used in commercial communication on Instagram, focusing on the account @dailyluxury_id. It also examines how these registers can be utilized in English language teaching. Using a qualitative descriptive method, the study analyzed 50 Instagram captions posted between January and March 2024. Content analysis was employed to identify and classify the registers based on word types (such as nouns and verbs) and their meanings, which were grouped into two categories: lexical (dictionary-based) and contextual (influenced by marketing purposes). The results show that 11 frequently used words appeared, with nouns (36.36%) and verbs (18.18%) being the most common, reflecting a focus on promotion and transaction. About 54.54% of the meanings followed standard dictionary definitions, while 45.45% had contextual meanings that conveyed urgency, exclusivity, or community engagement. For example, the word ready implies immediate availability, while local lovers create a sense of belonging. These language strategies contribute to a conversational yet persuasive tone that supports digital marketing goals. The study concludes that the use of registers on Instagram is purposeful and adapted to the target audience. It also suggests that such linguistic features can be integrated into English language teaching to expose learners to authentic, socially relevant materials—particularly in courses related to sociolinguistics, digital communication, or business English.